Demorest's Family Magazine - Demorest, William Jennings (New York: W. J. Demorest, 1897)
Demorest's Family Magazine. January 1897. Vol. 33, No. 3. -- The National Horse Show -- The First Snow -- A Dinner Engagement: A Closet Play in Two Acts -- Chinatown in New York -- Tales of Pierre and his People: The Gift of the Simple King -- Winter in Yellowstone Park -- Our Girls: The Curing of the College Graduate -- Is Chivalry Dead? -- Beginning in the Years -- Society Fads -- Home Art and Home Comfort: A Tulip Lampshade -- Household: The Weekly Mending -- A Fine Opportunity -- Sanitarian: Concerning the Teeth -- The World of Letters and Art -- The World's Progress -- About Women -- Mirror of Fashions: Review of Fashions - January -- Correspondence Club -- Gleanings: Concerning Wall-Paper
Mme Demorest's Mirror of Fashions
New York Illustrated News
Digitized from original print, Valdosta State University Archives and Special Collections, April 10, 2017. Ends on page 186.
Keywords: Magazines; Periodicals; Illustrated Periodicals; Women's History; Social History; Homemaking; Needlework; Travel; Fashion; Social History; 1800s; 19th Century